2022
DOI: 10.3389/fsurg.2022.1029028
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effect of channel assisted cervical key hole technology combined with ultrasonic bone osteotome in the treatment of single segment cervical spondylotic radiculopathy

Abstract: ObjectiveTo explore the clinical effect and operating skills of channel assisted Cervical Key Hole technology combined with Ultrasonic Bone Osteotome (CKH-UBO) in the treatment of single segment cervical spondylotic radiculopathy (CSR).MethodsFrom June 2018 to June 2020, 14 patients diagnosed with CSR and treated with channel assisted CKH-UBO were collected. The duration of the disease, the length of the incision, the operation time, the amount of bleeding during the operation, the length of hospitalization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The combination of the ultrasonic bone scalpel and the large channel maximizes the safety of UBO and eliminates the need for endoscope installation, further enhancing efficiency. Under the large channel, electric surgical knives and tools of the same size as those used in open surgery can be used to quickly remove soft tissues around the facet joints and vertebral plate edge [ 16 ], expanding the operative field and workspace. Simultaneously, the surgeon can manipulate the ultrasonic bone scalpel with one hand while using a retractor with the other hand to maintain a clear surgical field of view.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of the ultrasonic bone scalpel and the large channel maximizes the safety of UBO and eliminates the need for endoscope installation, further enhancing efficiency. Under the large channel, electric surgical knives and tools of the same size as those used in open surgery can be used to quickly remove soft tissues around the facet joints and vertebral plate edge [ 16 ], expanding the operative field and workspace. Simultaneously, the surgeon can manipulate the ultrasonic bone scalpel with one hand while using a retractor with the other hand to maintain a clear surgical field of view.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, with the introduction of UBO, the combination of a large channel approach and a microscope is no longer mandatory. A surgical approach using a large channel combined with UBO has been developed, potentially significantly improving the efficiency of MIS-PCF surgery [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a report by Zhang et al [ 29 ], of 42 patients with CSR who underwent key-hole surgery with O-arm navigation assistance, 38 achieved favorable treatment outcomes. Liu et al used ultrasonic bone osteotome as a supplementary approach in conjunction with key-hole surgery [ 7 ]. Previous reports have described the use of the novel Delta system for key-hole surgery [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned studies have demonstrated favorable clinical outcomes in terms of improving accuracy, relieving nerve compression, and reducing surgical time. However, they also have challenges such as complex utilization procedures, steep learning curves [ 7 ], high probability of postoperative complications [ 30 ], intraoperative radiation exposure [ 29 ], and inability to enhance the preoperative diagnostic confirmation rate of nerve root-type cervical spondylosis [ 7 , 29 , 30 ]. As a result, widespread adoption and application have not been achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation